Biomechanical evaluation on a new type of vertebral titanium porous mini-plate and mechanical comparison between cervical open-door laminoplasty and laminectomy: a finite element analysis - Lin, Zhiwei; Lin, Dongxin; Xu, Lin; Chen, Qiwei; Vashisth, Manoj Kumar; Huang, Xuecheng; Deng, Yuping; Zhang, Feihu; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Compare the spine’s stability after laminectomy (LN) and laminoplasty (LP) for two posterior surgeries. Simultaneously, design a new vertebral titanium porous mini plate (TPMP) to achieve firm fixation of the open-door vertebral LP fully. The objective is to enhance the fixation stability, effectively prevent the possibility of "re-closure," and may facilitate bone healing. Methods: TPMP was designed by incorporating a fusion body and porous structures, and a three-dimensional finite element cervical model of C2-T1 was constructed and validated. Load LN and LP finite element models, respectively, and analyze and simulate the detailed processes of the two surgeries. It was simultaneously implanting the TPMP into LP to evaluate its biomechanical properties. Results: We find that the range of motion (ROM) of C4-C5 after LN surgery was greater than that of LP implanted with different plates alone. Furthermore, flexion-extension, lateral bending, and axial rotation reflect this change. More noteworthy is that LN has a much larger ROM on C2-C3 in axial rotation. The ROM of LP implanted with two different plates is similar. There is almost no difference in facet joint stress in lateral bending. The facet joint stress of LN is smaller on C2-C3 and C4-C5, and larger more prominent on C5-C6 in the flexion-extension. Regarding intervertebral disc pressure (IDP), there is little difference between different surgeries except for the LN on C2-C3 in axial rotation. The plate displacement specificity does not significantly differ from LP with vertebral titanium mini-plate (TMP) and LP with TPMP after surgery. The stress of LP with TPMP is larger in C4-C5, C5-C6. Moreover, LP with TMP shows greater stress in the C3-C4 during flexion-extension and lateral bending. Conclusion: LP may have better postoperative stability when posterior approach surgery is used to treat CSM; at the same time, the new type of vertebral titanium mini-plate can achieve almost the same effect as the traditional titanium mini-plate after surgery for LP. In addition, it has specific potential due to the porous structure promoting bone fusion.